KEABSAHAN SEBUAH PERJANJIAN BERDASARKAN DARI KITAB UNDANG UNDANG HUKUM PERDATA - Eka Wijayanti, Ni Luh Putu; Sudiarta, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 12, November 2013, 2013)
In everyday social life, human beings can not be separated from a legal act. Man as a frequent subject of binding law themselves with others, that one of them could have been with a transaction. Binding in a transaction is an agreement between the parties to an agreement to be able to achieve a certain goal, which is called the agreement. But the general public does not really understand the importance of an agreement. Agreement is very importance to have in a transaction of any kind, which in making such an agreement would need to also concider how legitimate the terms of an agreement
Keywords: Agreement, Validity of the Agreement Terms, The Book of The Law of Civil Law